Power op-amp based active filter design with self adjustable gain control by neural networks for EMI noise problem - Gulez, K; Uzunoglu, M; Onar, OC; Vural, B (SPRINGER-VERLAG BERLIN, 2005)
An induction motor control system fed by an AC/DC rectifier and a DC/AC inverter group is a nonlinear and EMI generating load causes harmonic distortions and EMI noise effects in power control systems. In this paper, a simulation model is designed for the control circuit and the harmonic effects of the nonlinear load are investigated using FFT analyses. Also, the EMI noise generated by the switching-mode power electronic devices measured using high frequency spectrum scopes. An LISN based active filter is used to damp the harmonic distortions and EMI noises in the simulation environment. Neural network based control system is used to tune the power op-amp gain of series active filter to obtain the voltage value stability at the equipment side as well.
Keywords: Computer Science